Clinicopathological and Molecular Characteristics of Early-Onset Stage III Colon Adenocarcinoma: An Analysis of the ACCENT Database. (18th August 2021) - Jin, Zhaohui; Dixon, Jesse G; Fiskum, Jack M; Parekh, Hiral D; Sinicrope, Frank A; Yothers, Greg; Allegra, Carmen J; Wolmark, Norman; Haller, Daniel; Schmoll, Hans-Joachim; de Gramont, Aimery; Kerr, Rachel; et al.
Abstract: Background: Colon cancer (CC) incidence in young adults (age 20-49 years), termed early-onset CC (EO-CC), is increasing. Methods: Individual patient data on 35 713 subjects with stage III colon cancer from 25 randomized studies in the Adjuvant Colon Cancer ENdpoint database were pooled. The distributions of demographics, clinicopathological features, biomarker status, and outcome data were summarized by age group. Overall survival, disease-free survival, time to recurrence, and survival after recurrence were assessed by Kaplan-Meier curves and Cox models stratified by treatment arms within studies, adjusting for sex, race, body mass index, performance status, disease stage, grade, risk group, number of lymph nodes examined, disease sidedness, and molecular markers. All statistical tests were 2-sided. Results: Using a 5% difference between age groups as the clinically meaningful cutoff, patients with stage III EO-CC had similar sex, race, performance status, risk group, tumor sidedness, and T stage compared with patients with late-onset CC (age 50 years and older). EO-CC patients were less likely to be overweight (30.2% vs 36.2%) and more commonly had 12 or more lymph nodes resected (69.5% vs 58.7%). EO-CC tumors were more frequently mismatch repair deficient (16.4% vs 11.5%) and less likely to have BRAF V600E (5.6% vs 14.0%), suggesting a higher rate of Lynch syndrome in EO-CC. Patients with EO-CC had statistically significantly better overall survival (hazard ratio [HR] = 0.81, 95% confidence interval [CI] = 0.74 to 0.89; P  < .001), disease-free survival (HR = 0.91, 95% CI = 0.84 to 0.98; P  = .01), and survival after recurrence (HR = 0.88, 95% CI = 0.80 to 0.97; P  = .008) in the analysis without molecular markers; however, age at onset of CC lost its prognostic value when outcome was adjusted for molecular markers. Conclusion: Tumor biology was found to be a more important prognostic factor than age of onset among stage III colon cancer patients in the Adjuvant Colon Cancer ENdpoint database.